Grenada : 2022 Article IV Consultation-Press Release; Staff Report; and Statement by the Executive Director for Grenada. (IMF Staff Country Reports; Country Report ;, 2022)
Grenada's economy was hit hard by the pandemic, with a decline in real output of 14 percent in 2020 from both a collapse of tourism-related activities and the suspension of in-person classes at Saint George's University (SGU). Growth in 2021 is estimated to have partly recovered to 5.6 percent, driven by construction and agriculture. The authoritiesa' policy response helped mitigate the pandemic's impact through containment measures, increased health and social spending, and an expanded public investment program (including to build resilience to natural disasters). Central government debt rose to 70 percent of GDP in 2021 (from 59 percent in 2019) and the external position has worsened. The financial sector has so far weathered the crisis well.